In the Name of the Father: the Paternal Function, Sexuality, Law and Citizenship - Baron, Paula D (Victoria University of Wellington Law Review, 2006)
The purpose of this article is to examine the notion of legal paternal responsibility from the perspective of psychoanalytic theory. In psychoanalysis, a privileged place is accorded to the father, both in the emergence of the subject and in the symbolic order itself. This privileged position, however, flows not from the person of the father but from the performance of what Lacan terms the “paternal function”. Taking up this idea, the article considers the recommendations relating to legal paternity contained in the recent New Zealand Law Commission Report New Issues in Legal Parenthood. In particular, the article challenges the proposition that legal paternity should automatically flow from genetic fathering. The article argues that the assumption that there is or should be an inherent and natural link between genetic fathering and the responsibilities of legal parenting is fundamentally misconceivedÍ¾ will often discriminate against women, and, in particular, lesbian parentsÍ¾ and may be in conflict with the best interests of the child.